Avaliação da ação do methotrexate nas células em cultura de endométrio de mulheres com e sem endometriose - Kleine, João Paulo Ferreira de Oliveira [UNIFESP] (2015)
The Endometriosis is today a benign disease that affects about six million Brazilian. According to the Brazilian Association of Endometriosis, between 10% and 15% of women of reproductive age (13-45 years) can develop it and 30% are likely to become sterile. The disease is characterized by the presence of the endometrium, this tissue lining the uterus, outside the uterine cavity, or other organs of the pelvis as fallopian tubes, ovaries, intestines, and bladder. However, such growths may also occur in other parts of the body. The exact causes of endometriosis are unclear, but some possible causes for the problem are more speculated retrograde menstruation, growth of embryonic cells, poor immune system and many others. Although the setting is very well established, there are many features not defined yet endometriosis as its etiology, why cause infertility? Why some women complain of extreme pain and other not describe any pain? Why the disease affects so many different locations? And, along with other obscure features, which is the best treatment? This study aimed to define a possible treatment / action induced by chemotherapy by methotrexate in vitro cultures of endometrial cells, evaluating its role in proliferation, apoptosis and cell cycle of women endometrial cells with and without endometriosis after treatment. We selected 10 patients treated at Algia industry and Pelvic Endometriosis Department of Gynecology, Federal University of São Paulo, Paulista School of Medicine (UNIFESP-EPM) and Hospital São Paulo (HSP), 5 women with endometriosis grade IV (severe) indicating laparoscopic surgery and 5 women without any symptoms or suspected endometriosis to up the control study group. All after clinical examination or laparoscopy had a small portion of shaved endometrium / collected for in vitro culture of the same and subsequent treatment with methotrexate chemotherapy. The results show that the cultured cells showed a faster growth of patients with endometriosis compared to those of the control group independent of treatment. The initial evaluation with hormone therapy had no effect on the samples as much control as in endometriosis cells. Methotrexate has not decreased cell proliferation in both the control group and in the endometriosis group and the same has not demonstrated increased apoptosis in both the control group and in the endometriosis group.